Family Planning and the 2030 Agenda for Sustainable Development (Data Booklet) - United Nations (United Nations, 2019)
This booklet is based on the Estimates and Projections of Family Planning Indicators 2019, which includes estimates at the global, regional and country level of contraceptive prevalence, unmet need for family planning and SDG indicator 3.7.1 “Proportion of women who have their need for family planning satisfied by modern methods”.